Economic chromatographic methods for simultaneous quantitation of some fluoroquinolones and corticosteroids present in different binary ophthalmic formulations. Issue 7 (8th May 2020) - Saad, Martin N.; Essam, Hebatallah M.; Elzanfaly, Eman S.; Amer, Sawsan M.
Abstract: In this context, a simple RP-HPLC method is presented for the concurrent determination of Ofloxacin (OFX), Gatifloxacin (GFN), Dexamethasone sodium phosphate (DSP), and Prednisolone acetate (PA). The method has the strengths of being green, rapid, accurate, reproducible and cost-effective. The chromatographic separation utilized sodium phosphate as buffer with pH 3.0 ± 0.1 and acetonitrile 70:30 v/v for 3 min then reversing the ratio for the rest of the run with flow rate 1 mL min −1, Xselect ® C18 column and detection at 243 nm for DSP and PA, and 290 nm for OFX and GFN. Another chromatographic method was designed for the assay of the same drugs, namely TLC-Densitometric method. This method has the advance of being eco-friendly, simple and robust. The separation was obtained using mobile phase mixture of butanol/acetic acid/water (60:20:20 v/v/v) and normal phase silica gel plates as the stationary phase with simultaneous detection at 243 nm. The suggested methods can be adopted for the analysis of the four drugs in different binary combinations of eye drops saving money and solvents, and chemicals. They were validated with the guidance of ICH guidelines, with acceptable accuracy, precision, and selectivity. Graphical Abstract: